Day and night: diurnal phase influences the response to chronic mild stress - Aslani, Shilan; Harb, Mazen R.; Costa, Patrício S.; Almeida, Osborne F.; Sousa, Nuno; Palha, Joana A. (Frontiers in Behavioral Neuroscience, 2014)
Chronic mild stress (CMS) protocols are widely used to create animal models of depression. Despite this, the inconsistencies in the reported effects may be indicative of crucial differences in methodology. Here, we considered the time of the diurnal cycle in which stressors are applied as a possible relevant temporal variable underlying the association between stress and behavior. Most laboratories test behavior during the light phase of the diurnal cycle, which corresponds to the animal’s resting period. Here, rats stressed either in their resting (light phase) or active (dark phase) periods were behaviorally characterized in the light phase. When exposure to CMS occurred during the light phase of the day cycle, rats displayed signs of depressive and anxiety-related behaviors. This phenotype was not observed when CMS was applied during the dark (active) period. Interestingly, although no differences in spatial and reference memory were detected (Morris water maze) in animals in either stress period, those stressed in the light phase showed marked impairments in the probe test. These animals also showed significant dendritic atrophy in the hippocampal dentate granule neurons, with a decrease in the number of spines. Taken together, the observations reported demonstrate that the time in which stress is applied has differential effects on behavioral and neurostructural phenotypes.